2011
DOI: 10.1186/cc9410
|View full text |Cite
|
Sign up to set email alerts
|

Availability of critical care resources to treat patients with severe sepsis or septic shock in Africa: a self-reported, continent-wide survey of anaesthesia providers

Abstract: IntroductionIt is unknown whether resources necessary to implement the Surviving Sepsis Campaign guidelines and sepsis bundles are available in Africa. This self-reported, continent-wide survey compared the availability of these resources between African and high-income countries, and between two African regions (Sub-Sahara Africa vs. South Africa, Mauritius and the Northern African countries).MethodsThe study was conducted as an anonymous questionnaire-based, cross-sectional survey among anaesthesia providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
210
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(222 citation statements)
references
References 28 publications
9
210
2
1
Order By: Relevance
“…For example, it has been reported that approximately 37% hospitals in African and Sub-Saharan African countries have no access to lactate measurement (77). As a result, the diagnosis of septic shock involving lactate criterion cannot be readily made in substantial number of hospitals in LIMC.…”
Section: Special Considerations In Low-income and Middle-income Countmentioning
confidence: 99%
“…For example, it has been reported that approximately 37% hospitals in African and Sub-Saharan African countries have no access to lactate measurement (77). As a result, the diagnosis of septic shock involving lactate criterion cannot be readily made in substantial number of hospitals in LIMC.…”
Section: Special Considerations In Low-income and Middle-income Countmentioning
confidence: 99%
“…Admission into ICU may be required if the patient (Baelani et al, 2011;Dünser et al, 2006). The reported disease characteristics and mortality rates of patients admitted to ICUs in sub-Saharan Africa vary widely from one population to another (Oke, 2001;Okafor, 2009;Merah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason is that the guidelines have failed to incorporate the realities and inequities of different health-care systems and limitation of resources in developing countries. Baelani et al [5,9,17].…”
Section: Modify Surviving Sepsis Campaign Guidelinesmentioning
confidence: 99%